HeroeS - A Framework for Heterogeneous Software-Intensive System Design with SystemC - Becker, Markus; Müller, Wolfgang; Stroop, Joachim; Kiffmeier, Ulrich (Design, Automation and Test in Europe DATE, University Booth, Dresden)

Probabilistic Analysis of Long-term Swarm Performance under Spatial Interferences - Khaluf, Yara; Birattari, Mauro; Rammig, Franz-Josef (Theory and Practice of Natural Computing, Nr. 8273, 2nd International Conference on the Theory and Practice of Natural Computing, TPNC 2013)

Early Phase Memory Leak Detection in Embedded Software Designs with Virtual Memory Management Model - Joy, M. tech. Mabel Mary; Müller, Wolfgang; Rammig, Franz-Josef (Proceedings of AVICPS 2013, Dez. 2013 IEEE Computer Society,)

AN ENERGY-EFFICIENT HEURISTIC FOR HARD REAL- TIME SYSTEM ON MULTI-CORE PROCESSORS - He, Da; Müller, Wolfgang (Proceedings of International Conference on Applied Computing (AC))

Aspect-Oriented Model-Driven Engineering for Embedded Systems Applied to Automation Systems - Wehrmeister, Marco A.; Pereira, Carlos E.; Rammig, Franz-Josef (IEEE Trans. on Industrial Informatics vol. 9 (no. 4))
Automation and control systems include many “intelligent” automation devices, which are usually implemented as complex embedded systems. New methods and tools are demanded to cope with the increasing design complexity, while keeping the project on schedule. Proper handling of nonfunctional system requirements is a key factor during the design of industrial automation systems, since in some application domains they are as important as (sometimes, more important than) functional requirements. This paper presents a model-driven engineering approach, which combines Unified Modeling Language (UML) and aspect-oriented software development (AOSD) to design real-time and embedded automation systems. The proposed approach allows a smooth transition from the initial phases to implementation by using software tools, comprising the system specification and the automatic generation of source code. By combining UML with model-level aspects and a script-base code generation tool, it enables the use of AOSD during system design and implementation, even though the target platform does not natively support such concepts. Experimental results on using this approach to design real-world examples of automation systems are presented. The results indicate a positive impact on the design of automation systems. The encapsulation of nonfunctional requirements was improved, increasing the reuse of developed artifacts. Generated source code statistics indicate that the proposed approach can generated a fair amount of code per model element.

Task Allocation Strategy for Time-Constrained Tasks in Robots Swarms - Khaluf, Yara; Rammig, Franz-Josef (ECAL 2013, 12th European Conference on Artificial Life)

Simulationsgestützter Entwurf für Elektrofahrzeuge - Farshizadeh, Emad; Briese, Herrmann; Steinmann, David; Stockmann, Lars; Beringer, Steffen; Holler, Dominik; Klobedanz, Kay; Heinzemann, Christian; Peter, Klaus; Leuer, Michael (8. Dortmunder Autotag, Sep. 2013)
Das Thema Elektromobilität hat in der Fahrzeugindustrie in den letzten Jahren viel Aufmerksamkeit erhalten. Gerade im Bereich der Entwicklung von Steuergeräte-Software ist der Bedarf an frühzeitiger Absicherung hoch. Nur so können Produkteinführungszeiten minimiert und effektiv Entwicklungskosten eingespart werden. Komplexe Werkzeugketten und die verteilte Entwicklung erschweren den Prozess und verlängern die Entwicklungszeit. Das Förderprojekt „Simulationsgestützter Entwurf für Elektrofahrzeuge“, kurz „E-Mobil“, nimmt sich der Herausforderungen einer verteilten Entwicklung von Steuergeräte-Software an. Vier Projektpartner aus Industrie und Forschung untersuchen die Besonderheiten sowohl bzgl. des Entwurfsprozesses, als auch der beteiligten Entwurfswerkzeuge im Vergleich zur konventionellen Fahrzeugentwicklung. Im Fokus stehen die Modellierung und die simulationsgestützte Absicherung in frühen Entwurfsstadien. Die Modellierung umfasst Regelungssoftware sowie die für die Simulation nötigen elektrischen und mechatronischen Komponenten. Die vorliegende Arbeit stellt die Kernthemen sowie aktuelle Ergebnisse aus dem Projekt vor.

Efficient Power Intent Validation Using Loosely-Timed Simulation Models - Mischkalla, Fabian; Müller, Wolfgang (23rd International Workshop on Power And Timing Modeling, Optimization and Simulation, Sep. 2013)

Learning Recommendation System for Automated Service Composition - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 10th IEEE International Conference on Services Computing (SCC))
The as a Service paradigm reflects the fundamental idea of providing basic coherent functionality in terms of components that can be utilized on demand. These so-called services may also be interconnected in order to provide more complex functionality. Automation of this service composition process is indeed a formidable challenge. In our work, we are addressing this challenge by decomposing service composition into sequential decision making steps. Each step is supported by a recommendation mechanism. If composition requests recur over time and if evaluations of composition results are fed back, a proper recommendation strategy can evolve over time through learning from experience. In this paper, we describe our general idea of modeling this service composition and recommendation process as Markov Decision Process and of solving it by means of Reinforcement Learning. A case study serves as proof of concept.

Proteus Hypervisor: Full Virtualization and Paravirtualization for Multi-Core Embedded Systems - Gilles, Katharina; Grösbrink, Stefan; Baldin, Daniel; Kerstan, Timo (International Embedded Systems Symposium, 17. - 19. Jun. 2013)

On the Homogeneous Multiprocessor Virtual Machine Partitioning Problem - Grösbrink, Stefan (International Embedded Systems Symposium, 17. - 19. Jun. 2013)

Organic Real-time Programming – Vision and Approaches towards Self-Evolving and Adaptive Real-time Software - Rammig, Franz-Josef; Khaluf, Lial; Montealegre, Norma; Stahl, Katharina; Zhao, Yuhong (Proc. 9th Workshop on Software Technologies for Future Embedded and Ubiquitous Systems (SEUS) 2013)

HeroeS: Virtual Platform Driven Integration of Heterogeneous Software Components for Multi-Core Real-Time Architectures - Becker, Markus; Kiffmeier, Ulrich; Müller, Wolfgang (16th IEEE Computer Society Symposium on Object/Component/Service-oriented Real-time Distributed Computing)

A Framework for Enhancing Dependability in Self-x Systems by Artificial Immune Systems - Rammig, Franz-Josef; Stahl, Katharina; Vaz, Gavin Francis (Proc. 4th IEEE Workshop on Self-Organizing Real-Time Systems (SORT) 2013)

Multilevel Planning for Self-Optimizing Mechatronic Systems - Rasche, Christoph; Ziegert, Steffen (Proceedings of The Fifth International Conference on Adaptive and Self-Adaptive Systems and Applications)

AIS-based Anomaly Detection for Self-X Systems - Stahl, Katharina (Proceedings of the First Organic Computing Doctoral Dissertation Colloquium (OC-DDC'13))

Safe Self-Evolving Embedded Software via System Virtualization - Grösbrink, Stefan; Rammig, Franz-Josef (3rd SBC Workshop on Autonomic Distributed Systems - WoSiDA 2013)

Fair Bandwidth Sharing among Virtual Machines in a Multi-criticality Scope - Grösbrink, Stefan; Almeida, Luis; de Sousa, Mario; Petters, Stefan M. (5th Workshop on Adaptive and Reconfigurable Embedded Systems (CPSWeek 2013))

Accelerating Online Model Checking - Qanadilo, Mona; Samara, Sufyan; Zhao, Yuhong (6'th Latin-American Symposium on Dependable Computing (LADC 2013))

Bildangereicherte Kartenerstellung zur Unterstützung bei Rettungseinsätzen - Stern, Claudius; Rasche, Christoph; Kleinjohann, Lisa; Kleinjohann, Bernd (11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Statistisches Planen in einem realen Roboterszenario - Rasche, Christoph; Bieshaar, Maarten; Jungmann, Alexander; Kleinjohann, Lisa; Kleinjohann, Bernd (Entwurf mechatronischer Systeme, Verlagsschriftenreihe des Heinz Nixdorf Instituts, Paderborn, Band 310)

Architecture for Adaptive Resource Assignment to Virtualized Mixed-Criticality Real-Time Systems - Grösbrink, Stefan; Baldin, Daniel; Oberthür, Simon (ACM SIGBED Review, Band 10)

SystemC Verification Components - An enhanced OVM/UVM for SystemC - Kuznik, Christoph; F. S. Oliveira, Marcio; Müller, Wolfgang (edaWorkshop 13)

Funktionale Verifikation von Low-Power Designs unter Verwendung Virtueller Prototypen - Mischkalla, Fabian; Müller, Wolfgang (Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV))

SC OVM: An Advanced SystemC Library for OVM-based Verification - Kuznik, Christoph; F. S. Oliveira, Marcio; Müller, Wolfgang (Open SANITAS SystemC Verification Workshop)

Informationstechnik spart Ressourcen - Engels, Gregor; Gerth, Christian; Kleinjohann, Lisa; Kleinjohann, Bernd; Müller, Wolfgang (ForschungsForum Paderborn)

Basics of Virtual Machine Migration on Heterogeneous Architectures for Self-optimizing Mechatronic Systems - Necessary Conditions and Implementation Issues - Grösbrink, Stefan (Production Engineering Research & Development 7(1))

Learning Service Recommendations - Jungmann, Alexander; Kleinjohann, Bernd; Kleinjohann, Lisa (International Journal of Business Process Integration and Management 6(4))
The as a service paradigm reflects the fundamental idea of providing basic coherent functionality in terms of components that can be utilised on demand. These so-called services may also be interconnected in order to provide more complex functionality. Automation of this service composition process is indeed a formidable challenge. In our work, we are addressing this challenge by decomposing service composition into sequential decision making steps. Each step is supported by a recommendation mechanism. If composition requests recur over time and if evaluations of composition results are fed back, a proper recommendation strategy can evolve over time through learning from experience. In this paper, we describe our approach of modelling this service composition and recommendation process as Markov decision process and of solving it by means of reinforcement learning. A case study serves as proof of concept.

Systematic Application of UCIS to Improve the Automation on Verification Closure - Kuznik, Christoph; Oliveira, Marcio F.; Defo, Bertrand; Müller, Wolfgang (Proceedings of DVCON)

A 3D Path Planning Approach Extended by Bifurcation Theory for Formation Flights - Rasche, Christoph; Stern, Claudius; Kleinjohann, Lisa; Kleinjohann, Bernd (Recent Advances in Robotics and Automation, Studies in Computational Intelligence, Band 480)
After big disasters, search and rescue missions take place. During these missions it is essential to obtain an overview of the overall situation to arrange efficient rescue tasks as soon as possible. Afterwards, this information has to be continuously updated during the complete mission in order to quickly respond to changing conditions. The use of unmanned aerial vehicles (UAVs) is a viable choice to obtain such an overview in a fast and efficient way. Using multiple UAVs, the problem of coordination has to be solved to decrease the time needed to explore an area. We present an approach for the coordination of UAVs by setting up formation patterns using bifurcation theory. We combine this theory with a potential field approach for exploration, based on harmonic functions.

Fault-Tolerant Deployment of Real-Time Software in AUTOSAR ECU Networks - Klobedanz, Kay; Jatzkowski, Jan; Rettberg, Achim; Müller, Wolfgang (International Embedded Systems Symposium (IESS) 2013)

Automatic Reconstruction of Polygonal Room Models from 3D Point Clouds - Mertsching, Bärbel; Divband Soorati, Mohammad; Kotthauser, Tobias (IEEE International Conference on Robotics and Biomimetics (ROBIO))

Time delay implies cost on task switching: A model to investigate the efficiency of task partitioning - Hamann, Heiko; Karsai, Istvan; Schmickl, Thomas (Bulletin of Mathematical Biology)

Algorithmic Requirements for Swarm Intelligence in Differently Coupled Collective Systems - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Thenius, Ronald; Zahadat, Payam (Chaos, Solitons & Fractals)

Virtual Spatiality in Agent Controllers: Encoding Compartmentalization - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Schwarzer, Christopher; Michiels, Nico K.; Esparcia-Alcazar, Anna Isabel (Applications of Evolutionary Computation - 16th European Conference (EvoApplications 2013))

A Reductionist Approach to Hypothesis-Catching for the Analysis of Self-Organizing Decision-Making Systems - Hamann, Heiko (7th IEEE Int. Conf. on Self-Adaptive and Self-Organizing Systems (SASO 2013))

Speciation Dynamics: Generating Selective Pressure Towards Diversity - Hamann, Heiko; Lio, Pietro; Miglino, Orazio; Nicosia, Giuseppe; Nolfi, Stefano; Pavone, Mario (12th European Conference on Artificial Life (ECAL 2013))

Towards Swarm Calculus: Urn Models of Collective Decisions and Universal Properties of Swarm Performance - Hamann, Heiko (Swarm Intelligence)

Themenmodellierung zur Identifikation und Gruppierung von Spam-Webseiten - Laudemann, Stefan

Nichtapproximierbarkeitsresultate zu Radius- und Durchmesserclustering unter Verwendung von L_p-Metriken - Leder, Lennart

A heuristic energy-aware approach for hard real-time systems on multi-core platforms - He, Da; Müller, Wolfgang (Microprocessors and Microsystems - Embedded Hardware Design 37(6-7))

Embedded Systems: Design, Analysis and Verification. Proceedings of the 4th IFIP TC10 International Embedded Systems Symposium, IESS 2013, Paderborn, Germany, June 2013

Organic Programming of Real-Time Operating Systems - Khaluf, Lial; Rammig, Franz-Josef (The Ninth International Conference on Autonomic and Autonomous Systems)

Methods for the Design and Development - Anacker, Harald; Dellnitz, Michael; Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Horenkamp, Christian; Kleinjohann, Lisa; Kleinjohann, Bernd; Korf, Sebastian; Krüger, Martin; Müller, Wolfgang; et al. (Design Methodology for Intelligent Technical Systems Systems – Develop Intelligent Technical Systems of the Future)

Learning Efficient Information Extraction on Heterogeneous Texts - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the Sixth International Joint Conference on Natural Language Processing)

Information Extraction as a Filtering Task - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the 22nd ACM International Conference on Conference on Information & Knowledge Management)

Automatic Pipeline Construction for Real-Time Annotation - Wachsmuth, Henning; Rose, Mirko; Engels, Gregor (14th International Conference on Intelligent Text Processing and Computational Linguistics)

Practical algorithms for clustering and modeling large data sets - Analysis and improvements - Kuntze, Daniel

An Approach for Determining Optimal Contrast in Visual Cryptography - Juhnke, Jakob; Lefmann, Hanno; Strehl, Volker

Improved Side Channel Attacks on Pairing Based Cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Constructive Side-Channel Analysis and Secure Design)